THE EFFECT OF SPIRONOLACTONE IN IDIOPATHIC HIRSUTE WOMEN - DR.S.VIJAYALAKSHMI MD,; DR.M.SHANTHI MD, (International Journal of Pharma and Bio Sciences, 2013)
Idiopathic hirsutism also defined as peripheral hirsutism is a consequence of modified androgen metabolism at the peripheral level. An attempt has been made in the present work to study the clinical efficacy of spironolactone in diagnosed cases of idiopathic hirsutism, attending Endocrinology clinic, at Government Rajaji Hospital Madurai. The study has also been extended further to correlate its clinical efficacy to the plasma level of 3 α AdG as an easier and reliable diagnostic as well as prognostic approach to judge the androgenic activity in hirsute women. Spironolactone was administered in the dosage of 100 mg/day for 30 days in selected cases of idiopathic hirsute women and the plasma level of 3 α AdG is estimated before and after medication. The Study reveals an increase in 3 α AdG levels in the plasma after spironolactone therapy. It is found to be well correlated with the clinical improvement. During the study period of one month no disturbing side effects have been noticed.